Laboratory-developed Droplet Digital PCR Assay for Quantification of the JAK2V617F Mutation - Yupeng Liu; Cong Han; Jie Li; Shicai Xu; Zhijian Xiao; Zhiyun Guo; Shuquan Rao; Yao Yao (Global Medical Genetics, 2024)
Precise quantification of the JAK2V617F mutation using highly sensitive assays is crucial for diagnosis, treatment process monitoring, and prognostic prediction in myeloproliferative neoplasms' (MPNs) patients. Digital droplet polymerase chain reaction (ddPCR) enables precise quantification of low-level mutations amidst a high percentage of wild type alleles without the need for external calibrators or endogenous controls. The objective of this study was to optimize a ddPCR assay for detecting the JAK2V617F mutation and establish it as a laboratory-developed ddPCR assay in our center. The optimization process involved fine-tuning five key parameters: primer/probe sequences and concentrations, annealing temperature, template amount, and PCR cycles. Our ddPCR assay demonstrated exceptional sensitivity, and the limit of quantification (LoQ) was 0.01% variant allele frequency with a coefficient of variation of approximately 76%. A comparative analysis with quantitative PCR on 39 samples showed excellent consistency (r = 0.988).